Highly Efficient and Stable FAPbI3 Perovskite Solar Cells and Modules Based on Exposure of the (011) Facet - Zhang, Kai; Ding, Bin; Wang, Chenyue; Shi, Pengju; Zhang, Xianfu; Liu, Cheng; Yang, Yi; Gao, Xingyu; Wang, Rui; Tao, Li; Brooks, Keith G.; Dai, Songyuan; et al. (Nano-Micro Letters, 2023)
Perovskite crystal facets greatly impact the performance and stability of their corresponding photovoltaic devices. Compared to the (001) facet, the (011) facet yields better photoelectric properties, including higher conductivity and enhanced charge carrier mobility. Thus, achieving (011) facet-exposed films is a promising way to improve device performance. However, the growth of (011) facets is energetically unfavorable in FAPbI3 perovskites due to the influence of methylammonium chloride additive. Here, 1-butyl-4-methylpyridinium chloride ([4MBP]Cl) was used to expose (011) facets. The [4MBP]+ cation selectively decreases the surface energy of the (011) facet enabling the growth of the (011) plane. The [4MBP]+ cation causes the perovskite nuclei to rotate by 45° such that (011) crystal facets stack along the out-of-plane direction. The (011) facet has excellent charge transport properties and can achieve better-matched energy level alignment. In addition, [4MBP]Cl increases the activation energy barrier for ion migration, suppressing decomposition of the perovskite. As a result, a small-size device (0.06 cm2) and a module (29.0 cm2) based on exposure of the (011) facet achieved power conversion efficiencies of 25.24% and 21.12%, respectively. Highlights: 1 The (011) facet has excellent charge transport properties achieving closer alignment of energy levels. 2 By exploiting the (011) facet a device (0.06 cm2) and a module (29 cm2) achieved power conversion efficiencies of 25.24% and 21.12%, respectively.